Analisis Peran Animasi Menggunakan Aplikasi Macromedia Flash dalam Media Pembelajaran TIK di Kelas 11 SMA 1 Sungai Pua - Nur Syabillahtul Jannah; Hari Antoni Musri; Edgusnaldi Edgusnaldi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
In the midst of the rapid development of information and communication technology, education requires innovative transformations in learning methods. Animation has been recognized as an effective tool in enriching students' learning experiences through clear and interactive visual representations. The aim of this research is to analyze literature related to the use of animation as a learning medium, explore the advantages and challenges of its use, and convey the contribution of this research in the development of innovative learning practices. The method used in this research is a literature study, where data is obtained through analysis of theoretical sources and related research. The results of the literature study analysis show that animation has great potential to increase student learning motivation, involvement, creativity and personalized learning. However, it is important for educators and researchers to pay attention to good animation design and the role of educators in facilitating the effective use of animation. This research contributes to the development of innovative learning practices and enriches understanding of the use of animation as an effective learning medium in increasing student learning motivation